Jawapan

2015-06-13T12:52:39+08:00
X - 3y = 4
      x = 3y + 4

subtitusi
2x² - 9y² = 17
2(3y+4)² - 9y² = 17
2 (9y² +24y + 16) - 9y² = 17
18y² + 48y + 32 - 9y² = 17
18y² - 9y² + 48y + 32 - 17 = 0
9y² + 48y + 15 = 0

3y² + 16y + 5 = 0          ( diahagi 3)
(3y² + 15y) + (y+5) = 0        (difaktorkan)
3y (y+5) + 1(y+5) = 0
(3y+1) (y+5) = 0

3y + 1= 0
     3y = -1
     y₁ = -1/3
y + 5 = 0
     y₂ = -5         (tidak memenuhi)

y = -1/3   ⇒        x - 3y = 4
                    x - 3(-1/3) = 4
                           x + 1 = 4
                                 x = 3
x = 3 dan y = -1/3